Parameter Sensitivity Test of SWAT Hydrological Model On Two Different Resolutions (A Case Study of Upper Cisadane Subbasin, West Java) - Alim, Nurmaranti; Tarigan, Suria Darma; Tejo Baskoro, Dwi Putro; Wahjunie, Enni Dwi (JOURNAL OF TROPICAL SOILS, 2018)
A sensitivity analysis of SWAT parameters was conducted on different spatial resolutions. The sensitivity analysis aimed to determine the input parameters that have the most impact on the of output of the model. Resolution of different inputs in the SWAT analysis can produce different input parameters that can affect the output. The purpose of this study was to identify the level of sensitivity of the parameters used in the SWAT model simulated on two different resolutions, i.e. 1: 100,000 and 1: 250,000. A sensitivity test was conducted manually using the absolute sensitivity method, i.e. a method to test the sensitivity of the parameters of SWAT model that can change (either increase or decrease) one by one while the other parameters are constant. The results show that the Nash-Sutcliffe Efficiency (NSE) coefficients derived after calibration of the SWAT models on both resolutions of maps indicate similar performance of the models, with the category for the daily simulation of excellent (NSE coefficients of 0.55 and 0.54), while the monthly simulation is categorized as very satisfactory (NSE coefficients of 0.80 and 0.82). The sensitive parameters of the SWAT model identified in the current study include CN2 (initial SCS runoff curve number for moisture condition II), Alpha_BNK (flow recession constant or recession proportional to the banks of the river), CH_K2 (effective hydraulic conductivity in main channel alluvium), CH_N2 (Manningâ€™s â€œnâ€ value for the main channel), ESCO (soil evaporation compensation factor), GW_Delay (groundwater delay), and GW_Revap (groundwater â€œrevapâ€ coefficient).Â Â